ANALISA PENGARUH SISTEM INFORMASI EVALUASI KINERJA WARTAWAN (PT. INTI KHARISMA MANDIRI RIAU) - Irfaan Luqman Adi (Fakultas Sains dan Teknologi Universitas Islam Negeri Sultan Syarif Kasim Riau, 2018)
PT. Inti Kharisma Mandiri Riau (IKMR) or better known as Haluan Riau is one of the companies engaged in newspaper information. Information on each topic is derived from the facts of events and trusted sources covered by journalists. One of the constraints faced by Haluan Riau is the editorial section, which is the process of recapitulation of news that has not been integrated, namely the editorial secretary recapitulates every news published per day in Microsoft Excel. Then in the news recapitulation process published by every journalist who has not been in accordance with the Riau Procedure's permanent procedures. The prowess of Riau itself has a fixed procedure in the target news published from each of its reporters. Many reporters in the direction of Riau indirectly this causes difficulties in counting the number of news published by each journalist every month. So to overcome this problem will be built an information system for evaluating the performance of journalists in order to help in calculating the news published from each journalist quickly and accurately. Questionnaire data has an average value of 13 total respondents is 40.15 with a total standard deviation of 2,734. so that it can be concluded that the report on the performance of journalists is normally distributed.